Analisa Kualitas Layanan Sebagai Pengukur Loyalitas Pelanggan Dengan Spiritualisasi Marketing Sebagai Variabel Intervening (Studi Empiris pada CV AL-Muntaha Record Sragen) - Mulyanto, Mulyanto; Wahyuni, Sri (STIE AUB Surakarta)
This research aims to know: 1) the influence of a tangibles toward the spiritualisasi marketing, 2) the influence of a reliability toward the spiritualisasi marketing, 3) the influence of a responsiveness toward the spiritualisasi marketing, 4) the influence of a assurance toward the spiritualisasi marketing, 5) the influence of a emphaty toward the spiritualisasi marketing, 6) the influence of a tangibles toward the customer's loyalty, 7) the influence of a reliabilty toward the customer's loyalty, 8) the influence of a responsiveness toward the customer's loyalty, 9) the influence of a tangibles toward the customer's loyalty, 10) the influence of a e emphaty toward the customer's loyalty, 11) the influence of a spritualisasi marketing the customer's loyalty.Keywords: tangibles,reliability,responsiveness,assurance,emphaty and spiritualisasi marketing,customer's loyalty